Acid loaded porphyrin-based metal–organic framework for ammonia uptake. Issue 81 (26th August 2015) - Wilcox, Oliver T.; Fateeva, Alexandra; Katsoulidis, Alexandros P.; Smith, Martin W.; Stone, Corinne A.; Rosseinsky, Matthew J.
Abstract : A porphyrin-based metal–organic framework is shown to be structurally stable towards acid loading using either hydrochloric or formic acid. Abstract : A porphyrin-based metal–organic framework is shown to be structurally stable towards acid loading using either hydrochloric or formic acid. The capacity of this material as an ammonia sorbent was analysed using micro-breakthrough experiments in both dry and humid ammonia flows. The acid loaded material exhibited excellent uptake in comparison with the parent MOF.